Transitivité de l’action et ses expressions en trumai (langue isolée du Haut Xingú, Brésil) - Aurore Monod Becquelin; Cédric Becquey (Ateliers d'Anthropologie)
This article presents a preliminary approach to understanding the complex verbal system of the Trumai language, an isolated language of Upper Xingu (central Brazil). Composed of several transitive verb categories that contrastively pair agent-patient semantic roles and subject-object syntactic functions, the language is also characterised by the possible choice of one of two syntactico-semantic alignments within the limited framework of certain processes/scenarios, both involving agency.It is on the basis of the detailed study of a representative corpus of texts that we attempt to understand, from an agency viewpoint, what motivates the choice of one or another construction, and to show their main parameters. This exercise requires a consideration of the interface between language and culture, a place where the use of different meanings of the term “agency”—defined on linguistic, ethnologic and ethnolinguistic levels—constitute so many avenues for interpreting our data (transitivity and agents, the semantics of verbs, the position of the speaker in relation to the agents to whom he is speaking, the status of parameters as animacy or specificity).